Biotic Indicators for Ecological State Change in Amazonian Floodplains. (22nd June 2022) - Correa, Sandra Bibiana; van der Sleen, Peter; Siddiqui, Sharmin F; Bogotá-Gregory, Juan David; Arantes, Caroline C; Barnett, Adrian A; Couto, Thiago B A; Goulding, Michael; Anderson, Elizabeth P
Abstract: Riverine floodplains are biologically diverse and productive ecosystems. Although tropical floodplains remain relatively conserved and ecologically functional compared to those at higher latitudes, they face accelerated hydropower development, climate change, and deforestation. Alterations to the flood pulse could act synergistically with other drivers of change to promote profound ecological state change at a large spatial scale. State change occurs when an ecosystem reaches a critical threshold or tipping point, which leads to an alternative qualitative state for the ecosystem. Visualizing an alternative state for Amazonian floodplains is not straightforward. Yet, it is critical to recognize that changes to the flood pulse could push tropical floodplain ecosystems over a tipping point with cascading adverse effects on biodiversity and ecosystem services. We characterize the Amazonian flood pulse regime, summarize evidence of flood pulse change, assess potential ecological repercussions, and provide a monitoring framework for tracking flood pulse change and detecting biotic responses.